Nigeria : Request for a Two-Year Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents Nigeria's Request for a Two-Year Policy Support Instrument to support its reform efforts. All three tiers of government have adhered to a conservative oil price-based fiscal rule, resulting in large overall budget surpluses and a significant buildup of international reserves. The authorities have also initiated a broad structural reform program. GDP growth has been robust, benefiting from the improved macroeconomic environment and policy initiatives to spur agricultural production; and the medium-term growth outlook is favorable.